Governing Islam - Stephens, Julia Anne. (Cambridge ; New York)
xiii, 220 sayfa
Keywords: “Governing Islam traces the colonial roots of contemporary struggles between Islam and secularism in India, Pakistan, and Bangladesh. The book uncovers the paradoxical workings of colonial laws that promised to separate secular and religious spheres, but instead fostered their vexed entanglement. It shows how religious laws governing families became embroiled with secular laws governing markets, and how calls to protect religious liberties clashed with freedom of the press. By following these interactions, Stephens asks us to reconsider where law is and what it is. Her narrative weaves between state courts, Islamic fatwas on ritual performance, and intimate marital disputes to reveal how deeply law penetrates everyday life. In her hands, law also serves many masters - from British officials to Islamic jurists to aggrieved Muslim wives. The resulting study shows how the neglected field of Muslim law in South Asia is essential to understanding current crises in global secularism“ --